Association between single nucleotide polymorphism of immunoregulatory genes and preterm premature rupture of membranes in preterm labour - K. S. Liubomyrska; O. M. Kamyshnyi; Yu. Ya. Krut (Patologìâ)
Aim. Investigation of the association between SNP genes of IL4 (rs2243250), IL10 (rs1800896 and rs1800872) and RLN2 (rs4742076 and rs3758239) and preterm premature rupture of membranes in 26–34 weeks of gestation in Zaporizhzhia population.